Integrasi Tasawuf dan Psikologi dalam Pendekatan Psikoterapi Islam - Mirnani Denta Athiyah Uchtiyani (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to examine and formulate the integration of Sufism and psychology within the framework of Islamic psychotherapy as an effort to develop a holistic and contextually relevant therapeutic model. The background of this research is rooted in the limitations of conventional psychotherapeutic approaches that have not fully accommodated spiritual dimensions, particularly within Muslim communities. This study employs a qualitative approach using a library research method, involving the analysis and synthesis of relevant scholarly literature published over the last five years on Sufism, psychology, and Islamic psychotherapy. Data were collected from academic journal articles, scholarly books, and research documents, and analyzed through content analysis and thematic synthesis. The findings indicate that Sufism and psychology function as complementary disciplines in Islamic psychotherapy. The classical stages of Sufism, takhalli, tahalli, and tajall, can be systematically aligned with modern psychotherapeutic processes, ranging from psychological assessment to the evaluation of therapeutic outcomes. This integration positions Sufism as the spiritual foundation of therapy, while psychology provides the scientific and operational framework. The study concludes that integrating Sufism and psychology strengthens the biopsychosocial–spiritual paradigm of Islamic psychotherapy, offering both theoretical and practical contributions to the development of culturally and spiritually sensitive mental health services. Keywords: Integration, Islamic Psychotherapy, Psychology, Sufism